Role of earthworms in the degradation of grape marc: effects on chemical characteristics and microflora in the first steps of the process. - Gómez-Brandón, María; Lazcano, Cristina; Lores, Marta; Domínguez, Jorge (Instituto de Ecología, A.C., 2010)
The wine industry, of particular importance in various regions of Spain, generates vast amounts of organic waste during the different stages of wine production. Among the possible methodological alternatives available for its treatment, vermicomposting is one of the best-known processes for the biological stabilization of solid organic wastes by transforming them into safer and more stabilized materials suitable for application to soil. In this study we analyzed the chemical, biochemical and microbiological changes that occur in the first stages of the degradation of grape marc, an organic residue whose accumulation and management constitute an important environmental problem. After fifteen days of vermicomposting, a significant reduction in the fungal biomass measured as the ergosterol content was observed, as well as a reduction in microbial activity and cellulase and protease activities. The speed at which these transformations occurred makes vermicomposting a good system for studying the role of earthworms and their associated microflora in the first stages of grape marc degradation, providing important advances in the possible application of vermicomposting as an alternative for the treatment of organic residues derived from the wine industry.